Factors Affecting the Implementation of Patient Safety Culture at RSI Unisma Malang - Budi Susatia; Kusbaryanto Kusbaryanto; Sri Sundari; Chyntia Vicky Alvionita (Humanistic Network for Science and Technology (HNST), 2021)
Patient safety culture is an important aspect in providing quality health services. However, in Indonesia, many hospitals have not yet reported data on patient safety incidents. The purpose of this study was to determine the factors that influence the application of patient safety culture at RSI Unisma (Unisma Islamic Hospital), Malang. The research used was mix methods. Feelings of fear and anxiety were one of the biggest factors that can influence the application of a safety culture, especially incident reporting. Fear of being blamed could be caused by a patient safety culture that has not become a habit and has not been maximally socialized. Keywords: patient safety culture; patient safety; incident reporting